THE INFLUENCE OF BABY MASSAGE TO RICH MOTORIC DEVELOPMENT IN BABY AGES 0-12 MONTHS IN NADIAYU BABY CARE REGENCY IN GLODOGAN INDAH DISTRICT KLATEN - Walianty Fidyah Cendani; Witriyani .; Erlina Hermawati (STIKES DUTAGAMA KLATEN, 2018)
Background: Good stimulation for baby can be given by parents to optimize his/her potential development. Factors which are related to the children growth and development are sufficient nutrition and supportive family environment. Besides, from the children personal side, it can be given stimulation. One of the stimulation which is commonly done by parents is tactile stimulation in a form of baby massage. Objective:The aim of this study is too find out the influence of baby massage toward rough motoric development at the baby age 0 – 12 months old on Nadiayu baby care in Glodogan residence, Klaten. Research Method: This study used experiment method. The population of the research was the baby at 0 – 12 months old on Nadiayu baby care in Glodogan Indah residence, Klaten. There were 20 babies as the sample. The sample was taken by using purposive sampling. The instrument used in this study was Denver Developmental Screening Test(DDST). The data were analyzed by using wilcoxon test. Result: The rough motoric development at the baby age 0 – 12 month before giving treatment is delayed as big as 40 % and after giving treatment is normal (40%). The result of P value is 0,002 (P<0,05). Conclusion : There is influence of baby massage toward the rough motoric development at baby age 0 – 12 month on Nadiayu baby care in Glodogan Indah residence, Klaten.